Foreign Direct Investment, Portfolio Investment, Official Development Assistance and Labour Productivity in Nigeria - Uzoma Mirian Anyachebelu (ASHA Publishing, 2025)
Despite increasing inflows of foreign capital into Nigeria, labour productivity has remained relatively low, raising concerns about the effectiveness of such inflows in enhancing real economic performance. The study adopts the Solow-Swan neoclassical growth model to explain the relationship between labour productivity, capital, labour, and technology. It employs the ARDL framework, suitable for analyzing both short- and long-run dynamics, supported by FMOLS for robustness. The model incorporates international capital inflows and institutional quality, including interaction effects. Pre- and post-estimation tests ensure reliability. Using annual data (1992–2024), the study measures key variables from credible sources and applies E-Views (10) for estimation, ensuring accurate and consistent empirical analysis. The correlation matrix results indicate that the variables used in the study do not exhibit serious multicollinearity problems. Labour productivity (LP) shows positive correlations with several variables such as FDI (0.770), GFCF (0.797), RGDP (0.735), SERR (0.697), PRER (0.720), and INSQ_IDX (0.728), while FPI (-0.466) shows a negative relationship. The long-run ARDL results reveal that FDI (0.0345), ODA (0.096), external debt (0.1176), and institutional quality (1.7015) positively and significantly influence labour productivity. However, FPI (-0.0000) shows a negative but negligible effect. Interaction results indicate that institutional quality reduces the positive effects of FDI and external debt, while strengthening the positive effect of ODA on labour productivity in Nigeria. Diagnostic tests confirm the model is stable and free from autocorrelation and heteroscedasticity. The study concludes that improving institutional quality and ensuring efficient allocation of foreign capital are critical for enhancing labour productivity and achieving sustainable economic growth in Nigeria.